Dual low pass filter-based voltage sag detection for voltage sag compensator under distorted grid voltages - Sillapawicharn,Y. (2015)
© 2014 IEEE. In this paper, dual low pass filter (DLPF)-based voltage sag detection for voltage sag compensator under distorted grid is proposed. The conventional synchronously rotating reference frame (CSRRF)-based voltage sag detection is the most famous voltage sag detection method in the past. However it has a huge disadvantage as a long delay of detection time. The detection time is moderately improved by the improved modified synchronously rotating reference frame (IMSRRF)-based voltage sag detection. This paper presents DLPF-based voltage sag detection which is providing the shortest detection time when comparing to other methods. The performance of proposed voltage sag detection is verified via computer simulations in various conditions.